Not If but When : Adapting to Natural Hazards in the Pacific Islands Region - A Policy Note - Bettencourt, Sofia (Washington, DC: World Bank, 2022)
Pacific Island communities are particularly vulnerable to natural disasters - ranging from tropical cyclones, drought, floods, storm surges and tsunamis. Each year, these events result in significant loss of life, the destruction of homes, public infrastructure and livelihoods and the reversal of hard-won economic gains. Recently, deadly tsunami and earthquake events in the Indian Ocean region have focused the attention of the world community, particularly those living in small islands and coastal regions, to the need for greater vigilance in disaster prevention and preparedness. This is all the more important as evidence mounts that climate change will exacerbate the incidence of extreme events and potential disasters. The goal of this Policy Note is to influence policy makers and development partners in the Pacific Islands region to undertake risk management of natural hazards and minimize the future impacts of natural disasters, climate change and sea-level rise. As a short-term objective, the Policy Note aims to review the disaster trends and lessons learned from pilot risk management of natural hazards initiatives, and recommend a strategic way forward. Particular attention is paid to Incentives, Institutions, and Instruments.